Steel plate and method for manufacturing the same
Patent Information
- Application Number
- JP2026001982
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-01-08
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167450000004 
Figure 2026167450000001 
Figure 2026167450000002
Abstract
Description
[Technical Field]
[0001] This disclosure relates to steel plates and methods for manufacturing the same. [Background technology]
[0002] Traditionally, there has been a demand for improved occupant safety in vehicles, and to this end, the strength of vehicle body materials has been increased. On the other hand, against the backdrop of worsening global warming and other issues, the movement to improve the fuel efficiency of automobiles is accelerating. It is known that reducing the weight of the vehicle body is effective in improving fuel efficiency.
[0003] Hardened pipes used in door impact beams and other components also require further increases in strength to achieve both weight reduction and improved collision safety in automobiles.
[0004] The increased strength of quenched pipes presents the following two problems: (1) Increased strength (or increased amount of added elements associated with increased strength) makes the material more brittle, and cracks are more likely to occur when crushed. (2) During welding, carbon, which is important for ensuring strength and hardenability, diffuses from the weld to other areas, and variations in cooling rate occur within the weld HAZ, resulting in variations in strength within the weld HAZ.
[0005] For the reasons stated above, steel plates used to form quenched pipes are required to be able to achieve sufficient toughness and strength after quenching, and to sufficiently reduce strength variations within the welded heat-affected zone (HAZ).
[0006] Patent Document 1 proposes a steel sheet with excellent bendability in the range of 515 HV or higher in strength after quenching. Patent Document 2 proposes a steel sheet that can produce molded products with excellent balance of strength and toughness as well as hardness stability. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2017-155329 [Patent Document 2] Patent No. 7353768 [Overview of the project] [Problems that the invention aims to solve]
[0008] In the conventional techniques described in Patent Documents 1 and 2, the heating temperature for the quenching process is assumed to be as low as around 900°C. This is because if the heating temperature for the quenching process is too high, the austenite grain size increases and the toughness decreases.
[0009] However, in recent years, for the purpose of improving productivity and saving energy, quenching processes involving rapid heating using induction heating and short holding times of 10 seconds or less are sometimes implemented. In such cases, in order to ensure sufficient hardenability in a very short time, it is necessary to heat to extremely high temperatures of 950°C or higher, which raises concerns about a decrease in toughness.
[0010] As described above, in the conventional technologies described in Patent Documents 1 and 2, the heating temperature for the quenching treatment is assumed to be around 900°C, and no consideration has been given to suppressing the decrease in toughness when heated to high temperatures of 950°C or higher.
[0011] This disclosure has been made in view of the above circumstances, and one of its objectives is to provide a steel sheet and a method for manufacturing the same that can achieve sufficient toughness and strength even after quenching at a heating temperature of 950°C or higher, and that can sufficiently reduce strength variations within the weld HAZ. [Means for solving the problem]
[0012] One aspect of the present invention is: The component composition is, C: 0.15% by mass or more, 0.50% by mass or less, Si: 0.02 mass% or more, 2.5 mass% or less, Mn: 0.50 mass% or more and 5.0 mass% or less, Cr: 0 mass% or more and 1.2 mass% or less, Mo: 0 mass% or more and 0.25 mass% or less, P: more than 0 mass% and 0.030 mass% or less, S: more than 0 mass% and 0.020 mass% or less, Al: 0.010 mass% or more and 1 mass% or less, Ti: 0.005 mass% or more and 0.080 mass% or less, B: 0.0005 mass% or more and 0.0050 mass% or less, N: more than 0 mass% and 0.0100 mass% or less, and O: more than 0 mass% and 0.0020 mass% or less, the balance being Fe and unavoidable impurities, the metal structure containing ferrite, and satisfying the following formulas (1) and (2), the steel sheet. -1.52×G i -0.98×([Si]+[Mn]+[Cr])-43.5×[Mo]+27.7<15···(1) [Si]+[Mn]+[Cr]+[Mo]≧2···(2) In formulas (1) and (2), [Si], [Mn], [Cr] and [Mo] respectively represent the contents of Si, Mn, Cr and Mo expressed in mass%, and G i represents the average crystal grain size (μm).
[0013] Aspect 2 of the present invention is the steel sheet according to Aspect 1, further containing Ca: more than 0 mass% and 0.0040 mass% or less.
[0014] Aspect 3 of the present invention is Nb: more than 0 mass% and 0.040 mass% or less, V: more than 0 mass% and 0.30 mass% or less, Cu: more than 0 mass% and 0.30 mass% or less, Ni: more than 0 mass% and 0.30 mass% or less, Mg: more than 0 mass% and 0.010 mass% or less, and The steel sheet according to embodiment 1 or 2, further containing one or more selected from the group consisting of REM: greater than 0 mass% and 0.010 mass% or less.
[0015] Aspect 4 of the present invention is The average crystal grain size G i The steel plate is one of any one of embodiments 1 to 3, wherein the thickness is 2 μm or more.
[0016] Aspect 5 of the present invention is A step of preparing a steel billet having the component composition described in any one of embodiments 1 to 3 and satisfying formula (2), A method for manufacturing a steel sheet according to any one of embodiments 1 to 4, comprising the step of hot-rolling the steel billet at a rolling completion temperature of 900°C or higher. [Effects of the Invention]
[0017] According to this disclosure, it is possible to provide a steel sheet and a method for manufacturing the same that can achieve sufficient toughness and strength even after quenching at a heating temperature of 950°C or higher, and that can sufficiently reduce strength variations within the welded HAZ. [Brief explanation of the drawing]
[0018] [Figure 1] Figure 1 is a schematic diagram showing how to determine the intersection point in the average grain size measurement method. [Modes for carrying out the invention]
[0019] The inventors diligently conducted research to obtain a steel sheet that can achieve sufficient toughness and strength even after quenching at a heating temperature of 950°C or higher, and that can sufficiently reduce strength variations within the welded heat-affected zone (HAZ). As a result, they considered the following to be important: (a) Refining the crystal grains after quenching. (b) Compensate for the effects of reduced carbon content in the weld with other elements.
[0020] Regarding (a), the inventors considered that grain refinement after quenching is important for sufficient toughness after quenching. For grain refinement after quenching, in the case of a typical quenching treatment at around 900°C, it is considered effective to increase the number of grain boundaries, which are nucleation sites for recrystallization (i.e., to refine the grains before raising the temperature of the quenching treatment (hereinafter also simply referred to as "before quenching")). On the other hand, our own investigations have shown that in the case of quenching treatment at a heating temperature of 950°C or higher, an increase in nucleation sites leads to a decrease in Ac1 points, thus promoting grain growth and conversely resulting in coarser crystal grains after quenching. In other words, we have found that having coarse crystal grains before quenching is effective in refining crystal grains after quenching.
[0021] Furthermore, we focused on the effect of substitutional elements such as Si, Mn, Cr, and Mo on inhibiting grain boundary movement during quenching. In particular, we found that Mo, existing as precipitates with C and other elements, inhibits grain growth through a pinning effect. By quantitatively evaluating these effects, we determined the average grain size G after quenching. q We found that it can be expressed by the given formula (1). Note that G q If the thickness is less than 15 μm, sufficient toughness can be expected.
[0022] Regarding (b), as mentioned above, during welding, C may diffuse from the weld to other areas, causing its concentration to decrease. On the other hand, the inventors focused on the fact that the above-mentioned substitutional elements (Si, Mn, Cr, Mo) are also effective as substitutes for C, and found that by setting their total content to 2% by mass or more, it is possible to achieve sufficient strength (Vickers hardness of 450 or more) and to sufficiently reduce the strength variation within the weld HAZ (Vickers hardness variation of 25 or less). The details of each requirement specified in this embodiment are shown below. In this specification, unless otherwise specified, "steel plate" means a steel plate before quenching.
[0023] <1. Composition of steel sheet> The composition of the steel sheet according to this embodiment preferably includes C: 0.15% by mass or more, 0.50% by mass or less; Si: 0.02% by mass or more, 2.5% by mass or less; Mn: 0.50% by mass or more, 5.0% by mass or less; Cr: 0% by mass or more, 1.2% by mass or less; Mo: 0% by mass or more, 0.25% by mass or less; P: greater than 0% by mass, 0.030% by mass or less; S: greater than 0% by mass, 0.020% by mass or less; Al: 0.010% by mass or more, 1% by mass or less; Ti: 0.005% by mass or more, 0.080% by mass or less; B: 0.0005% by mass or more, 0.0050% by mass or less; N: greater than 0% by mass, 0.0100% by mass or less; and O: greater than 0% by mass, 0.0020% by mass or less, with the remainder being Fe and unavoidable impurities. The following provides a detailed description of each component.
[0024] (C: 0.15% by mass or more, 0.50% by mass or less) Carbon (C) is an element necessary to ensure the strength of steel plates after quenching. Therefore, the C content should be 0.15% by mass or more, preferably 0.18% by mass or more, and more preferably 0.20% by mass or more. However, if it exceeds 0.50% by mass, weldability deteriorates and LME cracking becomes more likely. Therefore, the C content should be 0.50% by mass or less, preferably 0.40% by mass or less, more preferably 0.38% by mass or less, and even more preferably 0.35% by mass or less.
[0025] (Si: 0.02 mass% or more, 2.5 mass% or less) Si improves hardenability, creates a martensitic structure in the base material and the welded area (including the HAZ area) where carbon decreases, and improves tempering softening resistance, thereby reducing strength variations. It also suppresses grain growth during quenching at temperatures above 950°C and contributes to grain refinement after quenching. Therefore, the Si content is 0.02% by mass or more, preferably 0.05% by mass or more. On the other hand, a high Si content leads to an increase in the Ac3 point, requiring even higher power during induction heating and resulting in greater energy loss. Therefore, the Si content is 2.5% by mass or less, preferably 2.4% by mass or less, more preferably 2.2% by mass or less, even more preferably 1.30% by mass or less, even more preferably less than 1.00% by mass, and particularly preferably less than 0.8% by mass.
[0026] (Mn: 0.50% by mass or more, 5.0% by mass or less) Mn exhibits similar effects to Si, and is particularly effective in improving hardenability. Therefore, the Mn content should be 0.50% by mass or more, preferably 1.0% by mass or more. On the other hand, adding a large amount of Mn makes blanking difficult. Furthermore, in cold rolling, the rolling load increases, and edge cracking becomes more likely. Therefore, the Mn content should be 5.0% by mass or less, preferably 4.5% by mass or less, more preferably 4.0% by mass or less.
[0027] (Cr: 0 mass% or more, 1.2 mass% or less) Cr is an element that may be added optionally. Cr exhibits similar effects to Si and Mn. The Cr content may be 0% by mass, but to achieve this effect, it is preferable to have more than 0% by mass, more preferably 0.01% by mass or more, and even more preferably 0.05% by mass or more. On the other hand, if the Cr content is excessive, the pickling properties in the pickling process after hot rolling will decrease. Furthermore, it will lead to an unnecessary increase in the strength of the steel sheet, reducing productivity during parts manufacturing. Therefore, the Cr content should be 1.2% by mass or less, more preferably 1.0% by mass or less, even more preferably 0.65% by mass or less, and even more preferably less than 0.6% by mass.
[0028] (Mo: 0 mass% or more, 0.25 mass% or less) Mo is an element that may be added optionally. Mo has the effect of improving hardenability and resistance to tempering softening, and is therefore effective in suppressing the decrease in strength of welded joints. Furthermore, by precipitating as carbides, it exhibits a pinning effect on recrystallization grain growth and contributes to grain refinement after quenching. The Mo content may be 0 mass%, but in order to exhibit this effect, it is preferable to have more than 0 mass%, and more preferably 0.05 mass% or more. On the other hand, if the Mo content is excessive, it will lead to an unnecessary increase in the strength of the steel sheet, for example, reducing productivity during manufacturing. Therefore, the Mo content should be 0.25 mass% or less.
[0029] (P: more than 0 mass%, 0.030 mass% or less) P is an unavoidable element. P is an element that segregates at grain boundaries and promotes grain boundary embrittlement. To avoid fracture during processing, decreased toughness, and reduced resistance to delayed fracture, it is recommended to reduce P as much as possible. Therefore, the P content should be 0.030 mass% or less, preferably 0.010 mass% or less.
[0030] (S: more than 0 mass%, 0.020 mass% or less) S, like P, is an unavoidable element that forms inclusions. To avoid breakage during processing, it is recommended to reduce S as much as possible. Therefore, the S content should be 0.020% by mass or less, preferably 0.010% by mass or less, and more preferably 0.005% by mass or less.
[0031] (Al: 0.010 mass% or more, 1 mass% or less) Al is an element that acts as a deoxidizing agent. To effectively exert this effect, the Al content should be 0.010% by mass or more, preferably 0.015% by mass or more. On the other hand, if the Al content is excessive, the strength after mold cooling will decrease, and the excessive generation of Al2O3 will lead to deterioration of low-temperature toughness. For this reason, the Al content should be 1% by mass or less, preferably 0.8% by mass or less, and more preferably 0.1% by mass or less. In this specification, the Al content refers to Al in a solid solution state (sol.Al).
[0032] (Ti: 0.005 mass% or more, 0.080 mass% or less) Ti has the effect of neutralizing N, which hinders the solid solution of B, by precipitating it as a Ti compound, in order to fully exhibit the effects of B described later. For this reason, the Ti content is 0.005% by mass or more, preferably 0.010% by mass or more, and more preferably 0.020% by mass or more. On the other hand, if the Ti content is excessive, it can lead to an unnecessary increase in the strength of the steel sheet due to the precipitation of carbides, etc., which can reduce productivity during manufacturing, for example. For this reason, the Ti content is 0.080% by mass or less, preferably 0.070% by mass or less, and more preferably 0.060% by mass or less.
[0033] (B: 0.0005 mass% or more, 0.0050 mass% or less) B is an element that improves hardenability and contributes to increasing the strength of steel sheets after quenching. To effectively achieve this effect, the B content should be 0.0005% by mass or more, preferably 0.0010% by mass or more, more preferably 0.0015% by mass or more, and even more preferably 0.0020% by mass or more. On the other hand, if the B content is excessive, it will lead to an unnecessary increase in the strength of the steel sheet, for example, reducing productivity during manufacturing. Therefore, the B content should be 0.0050% by mass or less, preferably 0.0040% by mass or less, and more preferably 0.0030% by mass or less.
[0034] (N: more than 0 mass%, 0.0100 mass% or less) N is inevitably present as an impurity element and can cause cracking during processing. Therefore, the N content should be 0.0100% or less, preferably 0.0060% by mass or less, and more preferably 0.0050% by mass or less.
[0035] (O: more than 0 mass%, 0.0020 mass% or less) O is inevitably present as an impurity element and can cause cracking during processing. Therefore, the O content should be 0.0020% by mass or less, preferably 0.0015% by mass or less, and more preferably 0.0010% by mass or less.
[0036] The steel sheet according to this embodiment contains the above-described component composition, and in one embodiment of the present invention, the remainder is preferably Fe and unavoidable impurities. As unavoidable impurities, the inclusion of elements introduced depending on the raw materials, materials, manufacturing equipment, etc., is permissible. For example, there are elements such as P, S, N, and O, which are generally preferable in smaller amounts and therefore unavoidable impurities, but whose composition range is separately defined as described above. For this reason, in this specification, "unavoidable impurities" constituting the remainder is a concept that excludes elements whose composition range is separately defined.
[0037] The steel sheet according to this embodiment may further contain the following optional additive elements.
[0038] (Ca: more than 0 mass%, 0.0040 mass% or less) Ca may be included as needed because it has the effect of suppressing the formation of MnS, which adversely affects delayed fracture resistance. This effect increases as the content increases, but in order to effectively exert the above effect, the Ca content is preferably greater than 0% by mass, and more preferably 0.0010% by mass or more. On the other hand, if the Ca content becomes excessive, the effect saturates and the cost increases. Therefore, the Ca content is preferably 0.0040% by mass or less, more preferably 0.0030% by mass or less, and even more preferably 0.0025% by mass or less.
[0039] (One or more selected from the group consisting of Nb: greater than 0 mass%, 0.040 mass% or less, V: greater than 0 mass%, 0.30 mass% or less, Cu: greater than 0 mass%, 0.30 mass% or less, Ni: greater than 0 mass%, 0.30 mass% or less, Mg: greater than 0 mass%, 0.010 mass% or less, and REM: greater than 0 mass%, 0.010 mass% or less) Nb may be included as needed because it contributes to improved strength and toughness by forming fine carbides and refining the crystal grains after quenching through a pinning effect. To achieve this effect, the Nb content is preferably greater than 0% by mass, and more preferably 0.0008% by mass or more. On the other hand, if the steel sheet contains an excess of Nb, coarse carbides are formed, which become the starting point for fracture and lead to deterioration of toughness. Therefore, the Nb content is preferably 0.040% by mass or less.
[0040] V forms fine carbides and, through a pinning effect, refines the crystal grains after quenching, contributing to improved strength and toughness. Therefore, it may be included as needed. To effectively exert this effect, the V content is preferably greater than 0% by mass, and more preferably 0.008% by mass or more. On the other hand, if V is present in excess in the steel sheet, coarse carbides are formed, which become the starting point for fracture and lead to a decrease in toughness. Therefore, the V content is preferably 0.30% by mass or less.
[0041] Cu is an effective element for improving the corrosion resistance of steel sheets and the delayed fracture resistance of components, and may be included as needed. To effectively achieve this effect, the Cu content is preferably greater than 0% by mass, and more preferably 0.01% by mass or more. On the other hand, if Cu is present in excess, it can cause defects on the surface of the steel sheet and the surface of the components, and can also be a factor in reducing pickling properties after hot rolling. Therefore, the Cu content is preferably 0.30% by mass or less.
[0042] Ni, like Cu, is an effective element for improving the corrosion resistance of steel sheets and the delayed fracture resistance of components, and may be included as needed. To effectively achieve this effect, the Ni content is preferably greater than 0% by mass, and more preferably 0.01% by mass or more. On the other hand, if Ni is present in excess, it can cause defects on the surface of the steel sheet and the component, and may also be a factor in reducing pickling properties after hot rolling. Therefore, the Ni content is preferably 0.30% by mass or less. Furthermore, it is more preferable that the total content of Cu and Ni be 0.50% by mass or less.
[0043] Mg may be included as needed because it has the effect of refining inclusions in the steel sheet and preventing cracks caused by inclusions during hot forming. To effectively exert this effect, the Mg content is preferably greater than 0% by mass, and more preferably 0.0008% by mass or more. On the other hand, if Mg is included in excess, its effect will saturate and the cost will increase. Therefore, the Mg content is preferably 0.010% by mass or less, and more preferably 0.008% by mass or less.
[0044] REM, like Mg, has the effect of refining inclusions in steel sheets and preventing cracks caused by inclusions during hot forming, and may be included as needed. To effectively exert this effect, the REM content is preferably greater than 0% by mass, and more preferably 0.0008% by mass or more. On the other hand, if REM is included in excess, its effect will saturate and the cost will increase. Therefore, the REM content is preferably 0.010% by mass or less, and more preferably 0.008% by mass or less.
[0045] <2. Metallographic structure of steel plate> The metal microstructure of the steel sheet according to the present embodiment includes ferrite. The ferrite fraction of the steel sheet according to the present embodiment is preferably more than 13 area%, more preferably 15 area% or more. Thereby, an unnecessary excessive increase in strength can be suppressed, and productivity during production can be ensured. The upper limit of the ferrite content is not particularly limited, and may be, for example, 99 area% or less, or 70 area% or less. The balance of the metal microstructure of the steel sheet according to the present embodiment may be any one or two or more selected from the group consisting of pearlite, bainite, retained γ, and martensite. Note that, in the present embodiment, the ferrite fraction shall be measured by the method of the examples described later.
[0046] <3. Formula (1) relating to the average grain size of the steel sheet after quenching treatment> As described above, the average grain size G (before the quenching treatment) i and substitutional elements of Si, Mn, Cr, Mo (particularly Mo) contribute to grain refinement after the quenching treatment at a heating temperature of 950°C or higher. The present inventors have found, based on the examples described later, that the effects of these parameters on grain refinement after the quenching treatment can be expressed as Formula (1). -1.52×G i -0.98×([Si]+[Mn]+[Cr])-43.5×[Mo]+27.7<15···(1) Here, in Formula (1), [Si], [Mn], [Cr] and [Mo] respectively represent the contents of Si, Mn, Cr and Mo in mass%, and G i represents the average grain size (μm).
[0047] The present inventors can accurately predict the average grain size G after the quenching treatment at a heating temperature of 950°C or higher from the left side of Formula (1), and by satisfying (1), the grains (prior austenite grains) after the quenching treatment can be sufficiently refined (specifically, G q can be made less than 15 μm), and it has been found that sufficient toughness can be achieved. The left side of Formula (1) is preferably less than 13. q can be made less than 15 μm), and it has been found that sufficient toughness can be achieved. The left side of Formula (1) is preferably less than 13.
[0048] (Average grain size G before quenching) i While not particularly limited as long as formula (1) is satisfied, a larger size is preferable, for example, 2 μm or more is preferred, and 3 μm or more is more preferred. In this embodiment, the average grain size G before quenching treatment is used. i and the average grain size G after quenching. q This shall be measured by the method described in the examples below.
[0049] <4. Equation (2) for compensating for the decrease in carbon content with another element> As described above, the inventors focused on the fact that Si, Mn, Cr, and Mo are effective as substitute elements for C, and found that by setting their total content to 2% by mass or more, it is possible to achieve sufficient strength (Vickers hardness of 450 or more) and to sufficiently reduce the strength variation within the weld HAZ (Vickers hardness variation of 25 or less). That is, the steel plate according to this embodiment satisfies the following formula (2). [Si]+[Mn]+[Cr]+[Mo]≧2···(2) Here, [Si], [Mn], [Cr], and [Mo] represent the content of Si, Mn, Cr, and Mo, respectively, expressed in mass percent. The left-hand side of equation (2) is preferably 2.3% by mass or more, and more preferably 2.6% by mass or more.
[0050] <5. Manufacturing method of steel plates> The method for manufacturing steel sheets according to this embodiment preferably includes the steps of preparing a steel billet having the above-described component composition and satisfying formula (2), and hot-rolling the steel billet at a rolling completion temperature of 900°C or higher. Each step will be described in detail below.
[0051] (Prepare steel billets) A steel billet having the above-mentioned component composition and satisfying formula (2) is prepared according to conventional methods. For example, a steel having the above-mentioned component composition and satisfying formula (2) is melted, and a steel billet (slab) is prepared by pouring the molten steel into a mold and performing continuous casting.
[0052] (Hot rolling process) The steel billet is hot-rolled according to a conventional method. For example, the steel billet obtained in the above process is placed in a heating furnace and heated to a predetermined temperature (e.g., 1200°C), and held at that temperature for a predetermined time (e.g., 30 minutes). Next, the heated steel billet is placed on a hot-rolling line. The steel billet is then passed sequentially between the rolls of the rolling stands of the roughing mill and the finishing mill to roll it into a steel plate with a predetermined thickness. At this time, the rolling completion temperature (FDT) is set to the average grain size G in order to satisfy equation (1). i The temperature is preferably high to increase the coefficient of heat transfer, for example, preferably 900°C or higher, and more preferably 910°C or higher. There is no particular upper limit, but it may be, for example, 1000°C or lower. After that, it is cooled to a predetermined temperature by air cooling or the like in a cooling device, and then wound up by a coiler. The winding temperature (CT) may be, for example, 400 to 700°C. After that, it is cooled to room temperature by air cooling or the like.
[0053] The method for manufacturing steel sheets according to this embodiment may include other steps insofar as it achieves the objectives of this disclosure. For example, the method for manufacturing steel sheets according to this embodiment may include a pickling step, a cold rolling step, and so on after the hot rolling step.
[0054] The steel plate according to this embodiment can achieve sufficient toughness and strength even after quenching at a heating temperature of 950°C or higher, and can also sufficiently reduce strength variations in the welded HAZ area, making it suitable for, for example, quenched pipes. [Examples]
[0055] The embodiment will be described in more detail below with reference to examples. This embodiment is not limited by the following examples, and can be implemented with appropriate modifications within the scope that is consistent with the spirit described above and below, and all such modifications are included within the technical scope of this embodiment.
[0056] Steel billets (slabs) having the chemical compositions shown for steel grades A to G in Table 1 were hot-rolled according to the method described above, under the conditions in Table 2 (rolling completion temperature (FDT) and coiling temperature (CT)) to obtain steel plates (samples for quenching treatment) for Tests No. 1 to 7. For Tests No. 5 to 7, descaling was performed by pickling after hot rolling, followed by cold rolling. In Table 1, "-" means that the element was not intentionally added and was present in amounts below the detection limit (unavoidable impurity level). In this specification, for elements other than impurities (Cu, Mo, Ca, etc.), "-" is considered to be "0 mass%", and for impurity elements (P, S, N, O, etc.), "-" is considered to be greater than 0 mass% but less than the detection limit (for S, greater than 0 mass% but less than 0.001 mass%).
[0057] [Table 1]
[0058] [Table 2]
[0059] The following evaluations were performed on the steel plates of Test No. 1 to 7 before the heat treatment.
[0060] (Ferrite fraction) For samples taken from between 1 / 4 and 3 / 4 of the width of the steel plate, the depth at the 1 / 4 position of the plate thickness (i.e., the position corresponding to a depth of 1 / 4 of the plate thickness from the surface of the steel plate) was determined by the point calculation method using images observed at 1000x magnification with a scanning electron microscope (SEM). Nital corrosion was used as the corrosion method.
[0061] (Average grain size Gi ) The L-shaped cross-section of the steel plate (i.e., the cross-section parallel to the rolling direction and the thickness direction) was etched to precipitate grain boundaries, and the area around the 1 / 4 position of the plate thickness was observed at 1000x magnification using a scanning electron microscope. Within a rectangular observation area of 100 μm in the rolling direction and 90 μm in the thickness direction, ten 100 μm line segments parallel to the rolling direction were drawn at 10 μm intervals in the thickness direction, and eleven 90 μm line segments parallel to the thickness direction were drawn at 10 μm intervals in the rolling direction. The points where these 21 line segments intersect with grain boundaries were measured, and the average grain size G was calculated by dividing the total length of the line segments (1990 μm) by the number of these intersections. i Figure 1 is a schematic diagram showing how to find the intersection. As shown in Figure 1, intersection 1 (indicated by "×") is the point where the grain boundary 2, shown by the solid line, and the line segment 3, shown by the dashed line, intersect.
[0062] Subsequently, the following evaluations were performed on the steel plates of Test No. 1 to 7, involving a quenching treatment with a heating temperature of 950°C or higher, in order to confirm the effectiveness of this embodiment.
[0063] (Average crystal grain size G after quenching treatment at a heating temperature of 950°C or higher) q ) The steel plate was heated to 960°C at a rate of 100°C / s and held for 10 seconds, and then cooled at a rate of 30°C / s to perform a quenching treatment. In the steel plate after this quenching treatment, the above-mentioned "average grain size G i Using the same method as for the evaluation of "[ ]", the points where 21 line segments intersect with grain boundaries (prior austenite grain boundaries after quenching) were measured, and the average grain size G was obtained by dividing the total length of the line segments (1990 μm) by the number of these intersections. q That's what I decided.
[0064] (Evaluation of strength and strength variation after quenching treatment at a heating temperature of 950°C or higher) To simulate the hardening process of the base material, a heat treatment of the base material was performed on the steel plate, and two types of heat treatments for the weld HAZ (heat-as-a-zone), 1 and 2, were performed using a Formaster testing machine as follows: Heat treatment of the base material: The steel plate is heated to 960°C at a rate of 100°C / s and held for 10 seconds, then cooled to room temperature at a rate of 30°C / s; Heat treatment of weld HAZ area 1: Heat the steel plate to 960°C at a rate of 100°C / s and hold for 3 seconds, then cool to room temperature at a rate of 100°C / s (simulating welding). Then heat again to 960°C at a rate of 100°C / s and hold for 10 seconds, then cool to room temperature at a rate of 30°C / s (simulating quenching). Heat treatment of weld HAZ area 2: Heat the steel plate to 960°C at a rate of 100°C / s and hold for 3 seconds, then cool to room temperature at a rate of 100°C / s (simulating welding). Then heat again to 960°C at a rate of 100°C / s and hold for 10 seconds, then cool to 360°C at a rate of 30°C / s, and each time cool to room temperature at a rate of 6°C / s (simulating quenching).
[0065] The Vickers hardness of the steel plates after each heat treatment was measured. The Vickers hardness was calculated as the average of three measurements taken at 1 / 4 of the plate thickness in the L-direction cross-section of the steel plate under a load of 1 kg. A Vickers hardness of 450 or higher for each heat-treated steel plate was judged to have sufficient strength. Furthermore, if the difference in Vickers hardness between heat treatments 1 and 2 of the welded HAZ was 25 or less, it was judged that the strength variation within the welded HAZ had been sufficiently reduced. Table 3 shows the evaluation results described above.
[0066] [Table 3]
[0067] The following can be seen from Table 3. Tests No. 1-2 and 5-7, which satisfy all the requirements specified in this embodiment, have an average grain size G after quenching. qThe average grain size G after heat treatment was less than 15, the Vickers hardness after each heat treatment was 450 or higher, and the difference in Vickers hardness between heat treatments 1 and 2 in the welded HAZ area was 25 or less. Therefore, the steel plates of tests No. 1-2 and 5-7 were able to achieve sufficient toughness and strength even after quenching at a heating temperature of 950°C or higher, and the strength variation within the welded HAZ area was sufficiently reduced. On the other hand, test No. 3 did not satisfy equation (1), so the average grain size G after quenching was not satisfied. q Since it was 15 or more and did not satisfy formula (2), at least one of the hardness values after each heat treatment was less than 450. Also, since test No. 4 did not satisfy formula (1), the average grain size G after quenching was less than 450. q Since the value was 15 or greater and equation (2) was not satisfied, at least one of the hardness values after each heat treatment was less than 450, and furthermore, the Vickers hardness difference between heat treatments 1 and 2 of the welded HAZ area was greater than 25. [Explanation of Symbols]
[0068] 1 Intersection 2. Grain boundaries 3 line segments
Claims
1. The component composition is, C: 0.15% by mass or more and 0.50% by mass or less, Si: 0.02% by mass or more, 2.5% by mass or less, Mn: 0.50% by mass or more, 5.0% by mass or less, Cr: 0 mass% or more, 1.2 mass% or less, Mo: 0% by mass or more and 0.25% by mass or less, P: more than 0 mass%, 0.030 mass% or less, S: more than 0% by mass, 0.020% by mass or less, Al: 0.010% by mass or more, 1% by mass or less, Ti: 0.005% by mass or more and 0.080% by mass or less, B: 0.0005% by mass or more and 0.0050% by mass or less, N: greater than 0 mass%, 0.0100 mass% or less, and O: more than 0 mass%, 0.0020 mass% or less, It contains, with the remainder being Fe and unavoidable impurities. The metal structure contains ferrite, A steel plate that satisfies the following equations (1) and (2). -1.52×G i -0.98×([Si]+[Mn]+[Cr])-43.5×[Mo]+27.7<15・・・(1) [Si]+[Mn]+[Cr]+[Mo]≧2...(2) In formulas (1) and (2), [Si], [Mn], [Cr], and [Mo] represent the content of Si, Mn, Cr, and Mo, respectively, expressed in mass percent. i This indicates the average crystal grain size (μm).
2. The steel sheet according to claim 1, further containing Ca: more than 0% by mass and 0.0040% by mass or less.
3. Nb: more than 0 mass%, 0.040 mass% or less, V: more than 0 mass%, 0.30 mass% or less, Cu: more than 0 mass%, 0.30 mass% or less, Ni: more than 0 mass%, 0.30 mass% or less, Mg: greater than 0% by mass, 0.010% by mass or less, The steel sheet according to claim 1 or 2, further containing one or more selected from the group consisting of REM: greater than 0% by mass and 0.010% by mass or less.
4. The average crystal grain size G i The steel plate according to claim 1 or 2, wherein the thickness is 2 μm or more.
5. A step of preparing a steel billet having the component composition described in claim 1 or 2 and satisfying formula (2), A method for manufacturing a steel sheet according to claim 1 or 2, comprising the step of hot-rolling the steel billet at a rolling completion temperature of 900°C or higher.
Citation Information
Patent Citations
Steel sheet for hardening and manufacturing method therefor
JP2017155329A
Steel sheets for hot stamping
JP7353768B2